Social Media and Lifestyle Effects on Purchase Intention among Millennial Coffee Consumers - Abdul Rahman Suleman; Ali Nurdin Siregar (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The growing coffee consumption among millennials, alongside the rising use of social media, has driven coffee shop businesses to optimize their digital marketing strategies. This study aims to analyze the influence of social media marketing and consumer lifestyle on millennials’ purchase intention toward coffee shops in Padangsidimpuan, Indonesia. A quantitative approach with a descriptive-associative design was employed. Data were collected through an online questionnaire distributed to 200 respondents aged 20–40 years who had previously seen coffee shop promotions via Instagram, TikTok, or Facebook. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM–PLS) with the assistance of SmartPLS 3.0 software. The results indicate that both social media marketing and consumer lifestyle significantly influence purchase intention. These findings emphasize the importance of aligning digital promotional strategies with the lifestyle preferences of target consumers to enhance brand appeal and customer loyalty. This research provides practical implications for coffee shop owners to develop marketing content that resonates with millennial lifestyles and suggests further studies across different regions and business sectors to improve the generalizability of the findings.